Nutrition and oncology: best practice and the development of a traffic light system. (2nd August 2021) - Atkinson, Emma; Atkinson, Judith
Abstract : Malnutrition is common in oncology patients, with age, disease stage and tumour type all influencing malnutrition risk. There are several detrimental effects of malnutrition in oncology patients, including weight loss, which is associated with negative oncological outcomes, and reduced survival. The causes of malnutrition in this group may be multifactorial and include effects from the tumour itself, altered metabolism, increased nutritional requirements, and cancer treatments and their associated side effects, which can impact on an individual's ability and desire to eat. Nutritional screening to identify early nutritional risk is essential and should involve the use of a validated screening tool, with commonly used tools usually assessing nutritional risk and weight loss over a period of months, for example a 3- to 6-month period. It is also important to consider weight changes over a shorter time period to identify rapid weight changes. Multidisciplinary teamworking is essential in tackling malnutrition, with collaborative working between the dietitians and the nutrition nurses shown to be beneficial in the authors' practice to develop community pathways and improve their service and manage increasing patient numbers. Malnutrition within oncology can often be managed with additional supplementation with oral nutritional supplements or enteral nutrition, where indicated. A low-volume, energy-dense, high-protein supplement can help to meet nutritional needs and to achieve dietetic aims, with compliance improved by the use of a low-volume product.